Fatigue in multilayered steels. (15th July 2020) - Kumar, Punit; Msolli, Sabeur; Jhon, Mark H.; Ramamurty, Upadrasta
Abstract: The high cycle fatigue behavior of two austenite/martensite multilayered stainless steel sheets, which only differ in terms of the surface layer, was investigated. While the quasistatic tensile stress-strain responses of both the sheets are nearly-identical, fatigue strength of sheets with austenitic outer layers is substantially higher than those with martensitic layers, due mainly to the nature of residual stress distribution in the two sheets. These results highlight the role of architecture on fatigue performance of hybrid materials. Graphical abstract: Image, graphical abstract